Unveiling Ubud’s Gastronomic Image through Comparative Aspect-Based Sentiment Analysis as Cross-Platform Insights and Strategic SWOT Perspectives - Ni Wayan Sumartini Saraswati; Ketut Jaya Atmaja; I Wayan Dharma Suryawan; Christina Purnama Yanti (International Journal of Engineering, Science and Information Technology, 2025)
Gastronomy is a strategic element in developing tourism destinations, and Ubud occupies a position as a cultural center that offers culinary riches of traditional value. This research reveals the gastronomic image of Ubud through a cross-platform analysis of TripAdvisor restaurant reviews and public opinion on sentiment labels at the micro level, implemented with VADER before fine-tuning aspect sentiment analysis (with BERT) to obtain a more granular representation. An in-depth analysis was conducted using wordcloud for cross-platform insights and SWOT recommendations. The research results show that the highest accuracy model evaluation results reached 98.87% for the term extraction aspect and 97.48% for the sentiment analysis aspect for TripAdvisor. Based on insight analysis, the food aspect is the main focus on both platforms, but with different narrative patterns: TripAdvisor emphasizes detailed evaluations such as taste, presentation, and service, while X is more oriented towards promotions, cultural identity, and participatory experiences, especially related to events such as the Ubud Food Festival. The integration of ABSA results into the SWOT framework resulted in four strategic findings: main strengths in the form of culinary authenticity, service quality, atmosphere, and experiential value; weaknesses related to inconsistencies in taste and chef quality; opportunities obtained from organizing festivals, street food, and culinary diversification; and threats in the form of overtourism and the perception of high prices. Overall, this study provides conceptual, methodological, and strategic contributions. The resulting findings strengthen the scientific basis for developing Ubud as a sustainable gastronomic destination that emphasizes taste, nature, and culture, as well as supporting data-based decision-making for tourism stakeholders.